In Search of the Ideal Tool for International School Teachers to Increase their Global Competency: An Action Research Analysis of the Global Competency Learning Continuum. (April 2020) - Carter, Adam
It is clear that if international school teachers are to be able to properly prepare students for a 21st century globalized workplace, they must first develop the global competence and intercultural skills needed to implement their students' development of global knowledge, skills and attitudes. Unfortunately, in many public schools and international schools, teachers do not possess the global competency needed to do so effectively. Since it can be expensive and ambitious to instill global competency in teachers on a school-wide, district-wide or nation-wide level, it may be more feasible for individual teachers to address their global competency deficit and take the necessary steps to improve it. There are several tools that can be used by individual teachers seeking to improve the awareness, skills and dispositions needed to become a truly globally competent teacher. This study focused on an innovative new tool, the Global Competency Learning Continuum (GCLC), which was designed for teachers and offers a resource library to help teachers address their shortcomings in twelve different levels of global competency. The research sought to ascertain whether the Global Competency Learning Continuum is an appropriate tool for international school teachers to use to assess and improve their global competency – or if there is a demand for an entirely new instrument that is more applicable to international school teachers. After reviewing research from surveys of international teachers, the data indicates that the Global Competency Learning Continuum is a promising and effective tool for use by international school teachers. It is the only tool designed specifically for teachers by a highly-respected educational institution, is free of charge and offers a valuable trove of resources for teachers who wish to actively improve their global competency.